Remote Glucose Monitoring Platform for Multiple Simultaneous Patients at Coronavirus Disease 2019 Intensive Care Units: Case Report including Adults and Children - Garelli, Fabricio (2021)
This work focuses on remote glucose monitoring at COVID-19 Intensive Care Units (ICU)in Argentina. We report the first cases using a new emergency platform for multi-centermulti-patient on-line remote glucose monitoring, which is accessible for everyone ondemand and which allows the integration of different glucose sensors. Five critical patientshave been monitored, two children and three adults, together with an ambulatory patient totest the platform versatility. All ICU patients have recovered or have been metabolicallycontrolled by the date of the submission of this report. Relevant lessons have been learnedfor the glucose management of critical patients, resulting in a new protocol in one of theparticipant hospitals.